Aborted sudden cardiac death in a young male with rheumatoid arthritis; case report - Kim, Narae; Cho, Sang-Ho; Yang, In-Ho (Journal of the Pakistan Medical Association, 2024)
Rheumatoid arthritis (RA) causes coronary artery atherosclerosis with a similar risk as diabetes or hypertension. However, coronary artery disease (CAD) is rare in young patients, especially in those presenting as chronic total occlusion (CTO). We report a rare case of aborted sudden cardiac death in a 26-year-old patient with a six-year history of RA. He had no cardiovascular risk factors apart from RA. He was diagnosed with severe ischaemic heart failure (HF) due to recent myocardial ischaemia with CTO, using multimodal evaluation. RA is associated with vulnerable plaque formation and prothrombotic tendencies. Anti-rheumatic drugs are thought to prevent the progression of CAD and reduce cardiovascular risk in patients with RA. However, this patient had severe HF with CTO, despite being on RA medication. This case suggests that RA may be a major risk factor for CAD, including CTO, in young individuals. Keywords: Rheumatoid Arthritis, Coronary Artery Disease, Sudden Cardiac Death, Myocardial Infarction.